2008
DOI: 10.1007/s10867-008-9100-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Interaction Among Nontoxic Phytoplankton, Toxic Phytoplankton, and Zooplankton: Emergence in Space and Time

Abstract: In homogeneous environments, by overturning the possibility of competitive exclusion among phytoplankton species, and by regulating the dynamics of overall plankton population, toxin-producing phytoplankton (TPP) potentially help in maintaining plankton diversity-a result shown recently. Here, I explore the competitive effects of TPP on phytoplankton and zooplankton species undergoing spatial movements in the subsurface water. The spatial interactions among the species are represented in the form of reactiondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…In contrast, cladocerans are generalist and non-selective grazers; thus, they are more vulnerable to intracellular toxins. Therefore, daphniids have developed various adaptations against the harmful effects of cyanobacteria (Ger et al, 2014), including behavioral responses that consist of avoiding areas with cyanobacterial blooms (Fulton and Paerl, 1987;Roy, 2008;Reichwaldt et al, 2013) and the physiological detoxification of ingested compounds (Pflugmacher et al, 1998). Our results indicate that large filter feeders were negatively correlated with the abundance of cyanobacteria genus Microcystis (number of 16sRNA gene copies), but results in respect to the relationship between zooplankton and biological activity of cyanobacteria were inconclusive (zooplankton correlation with PC2 axis, Tab.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In contrast, cladocerans are generalist and non-selective grazers; thus, they are more vulnerable to intracellular toxins. Therefore, daphniids have developed various adaptations against the harmful effects of cyanobacteria (Ger et al, 2014), including behavioral responses that consist of avoiding areas with cyanobacterial blooms (Fulton and Paerl, 1987;Roy, 2008;Reichwaldt et al, 2013) and the physiological detoxification of ingested compounds (Pflugmacher et al, 1998). Our results indicate that large filter feeders were negatively correlated with the abundance of cyanobacteria genus Microcystis (number of 16sRNA gene copies), but results in respect to the relationship between zooplankton and biological activity of cyanobacteria were inconclusive (zooplankton correlation with PC2 axis, Tab.…”
Section: Discussionmentioning
confidence: 68%
“…In dynamic ecosystems subjected to frequent toxic blooms, aquatic animals do not have to follow a predictable relationship proportional to cyanobacteria abundance, as has been demonstrated by Teegarden et al (2008) for copepods. This is especially the case when aquatic animal organisms are regularly exposed to MCs, triggering development of toxinresistant physiological mechanisms that weaken known behavioral (Ernst, 2008;Roy, 2008) or life-trait (Fulton and Paerl, 1987) responses. Nevertheless, further studies of the interactions between cyanobacteria, zooplankton and fish in sub-bloom conditions seems to be important in the face of observed climate change, where higher temperatures promote the growth rate of toxic cyanobacteria to a greater degree than that of nontoxic strains (Davis et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some species of phytoplankton can release poisons that affect zooplankton as well as possibly, directly or indirectly, also fish. Recent investigations have shown that movement can sustain inhomogeneous distribution levels of plankton communities composed of nontoxic phytoplankton, toxic phytoplankton and zooplankton, [3,10]. An idea that has been proposed for explaining the insurgence of red tides is that they are side effects caused by these toxin producing phytoplanktons, [4,5,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, spatial movements of planktonic systems in the presence of toxin-producing phytoplankton have been found to generate and maintain inhomogeneous biomass distribution of competing phytoplankton as well as grazer zooplankton [13].…”
Section: Introductionmentioning
confidence: 99%